2016
DOI: 10.1371/journal.pone.0150045
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds in Extra Virgin Olive Oil Stimulate Human Osteoblastic Cell Proliferation

Abstract: In this study, we aimed to clarify the effects of phenolic compounds and extracts from different extra virgin olive oil (EVOO) varieties obtained from fruits of different ripening stages on osteoblast cells (MG-63) proliferation. Cell proliferation was increased by hydroxytyrosol, luteolin, apigenin, p-coumaric, caffeic, and ferulic acids by approximately 11–16%, as compared with controls that were treated with one vehicle alone, while (+)-pinoresinol, oleuropein, sinapic, vanillic acid and derivative (vanilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 40 publications
5
50
2
Order By: Relevance
“…Oleuropein in an olive product provided increased OCN levels and improved bone mineral density levels after a 12‐month treatment, and no adverse effect was observed despite the long period of administration . However, a recent study reported no effect of oleuropein on osteoblast cell proliferation and suggested that the effects of oleuropein on bone metabolism occur via its anti‐inflammatory effect …”
Section: Discussionmentioning
confidence: 99%
“…Oleuropein in an olive product provided increased OCN levels and improved bone mineral density levels after a 12‐month treatment, and no adverse effect was observed despite the long period of administration . However, a recent study reported no effect of oleuropein on osteoblast cell proliferation and suggested that the effects of oleuropein on bone metabolism occur via its anti‐inflammatory effect …”
Section: Discussionmentioning
confidence: 99%
“…[35] Several studies conducted in vitro and in animal models have assessed the beneficial role of olive oil phenols on the formation and maintenance of bone through its modulation of both bone cell differentiation and function. [36][37][38] Oleuropein, tyrosol and hydroxytyrosol, the most abundant polyphenols in olive oil, have been related to several beneficial effects on bone metabolism in vitro an in animal models. [39] In humans, osteopenic subjects who consumed 250 mg/day of a polyphenol extract from Olea europaea for 12 months significantly increased their osteocalcin levels and stabilized lumbar spine BMD compared to a control group.…”
mentioning
confidence: 99%
“…In that sense, previous studies have demonstrated that exposure of osteoblasts to phenolic compounds in olive oil, such as, hydroxytyrosol, luteolin, apigenin, p‐coumaric, caffeic and ferulic acids, resulted in an increase in the number of cells in 24 hour. Other researches have studied different phenolic extracts which stimulated MG‐63 cell growth, and they induced higher cell proliferation rates than individual compounds …”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that phenolic compounds can modulate osteoblast cell functions . However, to our knowledge, no data are available on the ability of olive oil phenolic compounds to regulate cultured osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%